Sepak Terjang Bagus Rangin dalam Surat Dipati Natadireja Kepada Daendels (1808) - Titin Nurhayati Ma'mun; Hazmirullah Hazmirullah (Jumantara: Jurnal Manuskrip Nusantara, 2020)
In this article, we discuss a letter from a local official, named Raden Dipati Natadireja, to Governor-General Franco-Dutch Herman Willem Daendels (1808-1811). The letter written on 5 Jumadil akhir year of Dal 1223 AJ (July 25th, 1808) is a collection of the National Archives of the Republic of Indonesia and is coded ID-ANRI K66a, File 3569, Folio 39-42. Through the letter, Natadireja reported that many officials in Cirebon, especially low-ranking officials, joined the revolters. He also reported that the revolts were led by three respected figures, namely Kulur, Rangin, and Draham. In this research, the manuscript firstly was studied by using the philology theory that contain the method of manuscript study (codicology) and the method of text study (textology). Furthermore, the manuscript content was dialogued to the historical fact in the Cirebon Sultanate so that we obtained a complete understanding about context of writing the manuscript. The result shows that the wave of revolt had occurred since at least 1806 as the people of Cirebon could no longer stand the tyrannical treatment of colonial administration. On the other hand, the Chinese people actually get special treatment, especially in terms of land management.